Kajian Kepesindenan Sunda: Analisis Laras dan Surupan dalam Lagu “Tablo Kasmaran” Karya Eutik Muchtar - Marsel Ridky Maulana; Rifani Syahru Romadlana (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2025)
Purpose: The song “Tablo Kasmaran” is a musical repertoire in the form of sekar-gending that is often presented in Kliningan and Wayang Golek performances. The song “Tablo Kasmaran” was created by an artist named Eutik Muchtar, especially in the kepesindenan genre this song has a high musical difficulty. The purpose of writing this article is to reveal the song “Tablo Kasmaran” which has an extraordinary musical form, where the use of multi-laras and complex surupan varieties and has a deep poetic meaning. Methods: The method used is content analysis by analyzing documents from several video and audio recordings. Results and Discussion: Based on this method, it was found that the song “Tablo Kasmaran” uses multi-laras based on three laras namely “Salendro”, “Degung” and “Madenda” and the Surupan of this song counts four namely, Salendro 1 = Tugu, Madenda 4 = Tugu, Madenda 4 = Panelu, and Degung 2 = Tugu. Conclusion: From the results of the study conducted, the song “Tablo Kasmaran” in its presentation is a combination of musical and vocal aspects as well as a combination of multi-laras and surupan variety. The song “Tablo Kasmaran” has a tight complexity structure and when impregnated the melodies of this song are very beautiful, besides having beauty in terms of lyrics, this song has a deep meaning of rumpaka (poetry).